THE MENTAL HYGIENE APPROACH IN THE PERSONALITY DEVELOPMENT PROCESS FOR THE MENTAL HEALTH OF INMATES AT THE NARCOTICS CLASS IIA PRISON IN MUARA BELITI - Iswar Iswar; Meitisa Vanya Simanjuntak (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study explores the application of a mental hygiene approach in personality development to improve the mental health of inmates at the Class IIA Muara Beliti Narcotics Correctional Institution. The research focuses on how the mental hygiene program is implemented and the obstacles encountered in its execution. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that the rehabilitation program—consisting of counseling, mental health education, and stress management activities—has a positive impact on inmates by helping them manage emotions, reduce stress, and improve overall psychological well-being. However, the implementation of the program is still constrained by several challenges, including limited facilities, a shortage of professional mental health staff, and the presence of social stigma among inmates. These factors reduce the overall effectiveness of the program. In conclusion, although the mental hygiene approach has been implemented fairly well and shows positive outcomes, further improvements are needed, particularly in enhancing facilities, increasing the availability of trained personnel, and addressing stigma, to optimize the effectiveness of mental health development programs in correctional institutions. Keywords: Mental Hygiene; Prisoner Rehabilitation; Mental Health; Personality Development